2022
DOI: 10.3390/cells11111824
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Plasticity in Inflammation: Insights into Description and Regulation of Immune Cell Phenotypes

Abstract: Inflammation is a life-saving immune reaction occurring in response to invading pathogens. Nonetheless, inflammation can also occur in an uncontrolled, unrestricted manner, leading to chronic disease and organ damage. Mechanisms triggering an inflammatory response, hindering such a response, or leading to its resolution are well-studied but so far insufficiently elucidated with regard to precise therapeutic interventions. Notably, as an immune reaction evolves, requirements and environments for immune cells ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 291 publications
0
18
0
Order By: Relevance
“…This indicated that a smaller entry door size did not pose a significant barrier to the cell infiltration, which can be due to the high plasticity of immune cells. [ 19 ] Macrophages and FcεRI+ cells (such as Langerhan cells [LC], monocytes, mast cells, and other dendritic cells [DC]) dominated the immune cell infiltration during the implantation [ 20 ] (Figure 2c). The immune cell recruitment followed a size‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that a smaller entry door size did not pose a significant barrier to the cell infiltration, which can be due to the high plasticity of immune cells. [ 19 ] Macrophages and FcεRI+ cells (such as Langerhan cells [LC], monocytes, mast cells, and other dendritic cells [DC]) dominated the immune cell infiltration during the implantation [ 20 ] (Figure 2c). The immune cell recruitment followed a size‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of peripheral immune cells can induce two different phenotypes – anti-inflammatory or pro-inflammatory states – depending on stimulator patterns [40]. The classic pro-inflammatory phenotype is characterised by activation of the NF-κB pathway, and increased production and release of the proinflammatory cytokines TNF, IL-1 and IL-6 [41, 42]. Although the increase in PBMCs NF-κB levels were not significant in this study, ACTH-treated animals had increased serum levels of IL-6 when compared to saline-treated controls, demonstrating an increase in proinflammatory signalling in the present model.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage efferocytosis of apoptotic PMNs is an essential cellular response to enhance the clearance of infection and the resolution of inflammation. 38,39 Pro-resolving mediators are potent bioactive agonists and regulators of macrophage efferocytosis of apoptotic neutrophils in both human cells and murine models of inflammation. 39 We set out to determine if 4S,5R-RCTR1 enhances M2-like macro-…”
Section: Synthetic 4s5r-rctr1 Increases Efferocytosis Of Apoptotic Ne...mentioning
confidence: 99%